Competency Testing for Teacher Certification. Information on Personnel Supply and Demand - National Clearinghouse for Professions in Special Education, Reston, VA.; National Clearinghouse for Professions in Special Education, Reston, VA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
Information on competency testing for teacher certification is reprinted exactly from four pages (70-71, 129-130) of a National Center for Education Statistics Publication (volume I of "The Condition of Education: Elementary and Secondary Education 1988," edited by J. D. Stern.) As of the fall of 1987, 45 states had enacted competency testing programs as part of the process of initially certifying teachers. In 31 states, regulations also required that students take an examination in order to be admitted to a teacher education program. Briefly described are subject coverage of competency tests, attitudes toward competency testing, and alternative routes to certification. A United States map is used to illustrate which states have and have not enacted testing programs for initially certifying teachers. In addition, a table lists the year each state enacted a testing program, the year the program became effective, and the test used. (JDD)
Sponsoring Agency: Office of Special Education and Rehabilitative Services (ED), Washington, DC.
Contract Number: G0087C305388.
ERIC Note: Prepared by the Supply/Demand Analysis Center.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Elementary Secondary Education; Minimum Competency Testing; State Programs; State Standards; Teacher Certification; Teacher Evaluation; Testing Programs; Numerical/Quantitative Data; Reports, Descriptive